Metabolic changes in normal appearing white matter in multiple sclerosis patients using multivoxel magnetic resonance spectroscopy imaging. Issue 14 (April 2017) - Sun, Jubao; Song, Hao; Yang, Yong; Zhang, Kun; Gao, Xiuju; Li, XiaoPan; Ni, Li; Lin, Pan; Niu, Chen
Abstract : Abstract: Demyelination and axonal degeneration caused by multiple sclerosis (MS) exist in the white matter and not only in the lesion area. Magnetic resonance spectroscopy (MRS) could provide a unique insight into metabolic changes in the normal appearing white matter (NAWM). To evaluate the subtle axonal degeneration and delineate the spatial distribution of metabolite abnormalities in the NAWM in patients with MS. A total of 17 clinically definite relapsing-remitting MS (RRMS) patients and 21 healthy controls were enrolled in this study. 2D 1H magnetic resonance spectroscopic imaging (MRSI) performed at 3 Tesla was used to measure metabolite concentrations in the frontal-parietal-occipital NAWM. Ratios of N-acetyl-aspartate (NAA) and choline (Cho) to creatine (Cr) and Cho to NAA were calculated in each voxel. MS patients showed decreased NAA/Cr and increased Cho/NAA ratios in the NAWM compared to healthy controls. In the parietal NAWM, the extent of NAA/Cr decrease was significantly higher than that in the frontal and parietal-occipital NAWM. Decreased NAA in the NAWM would provide useful metabolic information for evaluation of disease progression in MS. The high extent of NAA decrease in the parietal NAWM helps improve the accuracy of the prediction. Abstract : Supplemental Digital Content is available in the text